DESIGN OF AN ISLAMIC CENTER WITH ISLAMIC ARCHITECTURAL THEME IN KEBOMAS DISTRICT, GRESIK REGENCY, EAST JAVA - Prakoso, Gerhana Bagas; Widjajanti, Wiwik Widyo; Hendra, Failasuf Herman (Faculty of Civil Engeneering and Planning - ITATS, 2025)
The design of the Islamic Centre in Gresik Regency responds to the growing need for a multifunctional facility that supports worship, education, social interaction, and economic activities. As a city known for its strong Islamic culture and history, Gresik often referred to as a santri city requires a public space that promotes integrated religious outreach (dakwah) and education. Located on Veteran Road No. 233, a key route linking Gresik and Surabaya, the site offers strategic accessibility. The core issue addressed in this project is the absence of a comprehensive facility that unifies Islamic activities in one location. The community seeks a space that reflects their identity and meets contemporary needs while remaining rooted in Islamic values. The planning process involved a literature review, case studies, site observations, and spatial needs analysis. The design adopts Islamic architectural principles, guided by the macro concept of Rahmatan lil ‘alamin (a mercy to all creation). This overarching theme shapes three micro concepts: land use that reflects hablumminaalam (relationship with nature), building forms inspired by hablumminallah (relationship with God), and spatial organization aligned with hablumminannas (relationship with fellow humans). The final design presents an integrated Islamic Centre complex with clearly defined zoning, featuring a mosque, Islamic Centre building, educational facility, and Hajj training area (manasik haji), along with supporting elements such as a zakat management office, canteen, and green open spaces. The architectural and interior design emphasizes Islamic aesthetics, efficient circulation, and comfort for users engaging in religious and community activities. Ultimately, this Islamic Centre aims to serve not only as a spiritual hub but also as an educational, social, and economic resource. Designed with contextual relevance and sustainability in mind, the building aspires to become an enduring symbol of Islamic architecture and a meaningful contribution to Gresik’s cultural development.